2021
DOI: 10.1101/2021.04.05.21254819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of specific antibodies against SARS-CoV-2 in breast milk of lactating women vaccinated with an mRNA vaccine

Abstract: INTRODUCTION The recent approval of vaccines against COVID–19 has generated great concern among breastfeeding women, since these patients were excluded from vaccination clinical trials. The present study aimed to analyze the levels of specific SARS–CoV–2 antibodies in breast milk of mRNA–vaccinated women across time and their correlation with serum antibody levels. METHODS Prospective study including lactating women aged over 18 who were vaccinated against SARS–CoV–2 with the Pfizer–BioNTech® COVID–19 vacci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Esteve-Paula et al 23 18/18 (IgG-S1) 18/18 (IgG-S1) N/A Taken together, the studies from Friedman et al 27 and Esteve-Palau et al 23 suggest that peak antibody titers may occur as early as 7 days after the second dose and last as long as 28 days after the second dose.…”
Section: N Positive/n Tested (Antibody-antigen)mentioning
confidence: 88%
See 1 more Smart Citation
“…Esteve-Paula et al 23 18/18 (IgG-S1) 18/18 (IgG-S1) N/A Taken together, the studies from Friedman et al 27 and Esteve-Palau et al 23 suggest that peak antibody titers may occur as early as 7 days after the second dose and last as long as 28 days after the second dose.…”
Section: N Positive/n Tested (Antibody-antigen)mentioning
confidence: 88%
“…Eight studies noted an increase in IgG, IgM, and/or IgA in the sera of pregnant and lactating individuals after vaccination. 16,18,[22][23][24][25][26][27] Gray et al 18 observed that IgM and IgA titers were strongly induced after the first dose in 115 pregnant and lactating individuals. IgG was robustly induced after both doses, and by 2 weeks after the second vaccine, the dominant serum antibody response was IgG.…”
Section: Temporal Profile Of Humoral Responsementioning
confidence: 99%
“…Pregnant and lactating women were excluded from initial clinical trials for anti-SARS-CoV-2 vaccination, and many concerns, especially safety issues, arose related to vaccination in this specific population. To our knowledge, only a few studies have addressed this topic [12][13][14][15]. To date, there are no robust studies regarding the safety and efficiency of vaccination in lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…However, information on their dynamics after vaccination remains limited. While accumulating data are being provided for mRNA-based vaccines 12,19,20 , no information is available for the adenovirus-based vaccine (AstraZeneca).…”
Section: Discussionmentioning
confidence: 99%